THEATER OF IVAN FRANKO: ARTISTIC PHENOMENON AND AESTHETICALLY BEAUTIFUL PHENOMENON - Horob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article an attempt is made to explore the phenomenon of artistic and aesthetic phenomenon of the Ukrainian national culture, including literature and theater, "Ivan Franko Theater" in particular. On wide drama and critical material Ivan Franko’s theatrelogical concepts are discovered, his dramatic layer of creativity is examined, the role of the writer and scholar in the development of Ukrainian literature-stage process of 19-20 centuries from new theoretical and methodological position is researched.